ANALISIS PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING - Vincensia Arinda, Sugi Suhartono (Jurnal Akuntansi, 2018)
Accounting information in the form of financial statements is expected to describe the actual condition of the company. Information such as profitability, tax avoidance, company value is one of the many information used in measuring company performance. The grand theories of this research are agency theory and signal theory.The population in this research are 9 manufacturing companies listed in Indonesia Stock Exchange 2011-2015, into a total of 45 samples of the company. Data analysis techniques used are pooling test, classical assumption test, descriptive statistical test, F-test, t-test, and coefficient determination of R square. And data obtained from www.idx.co.id and www.finance.yahoo.com. This research proven that there is enough evidence that profitability affects to tax avoidance, there is not enough evidence that profitability affects relevance to company value, there is sufficient evidence that tax avoidance affects to company value, and there is enough evidence that tax avoidance is a mediation between profitability and company value.Â Key words: Profitability, Tax Avoidance, Company Value